Performance Professionalism Employee Secretariat Regional People's Representative Council (DPRD) Cimahi City - Irawan, Ade (Jurnal Sosial Sains dan Komunikasi, 2023)
According to the Law of the Republic of Indonesia Number 23 of 2014 concerning Regional Government it is stated that City and Regency DPRD Secretaries are led by a City and Regency DPRD Secretary who is appointed and dismissed by decree of the Regent or Mayor with the approval of the Chairperson of the regency/city DPRD after consulting with the faction leaders. In accordance with statutory provisions in Cimahi City, West Java Province, one of which is the Secretary of the Cimahi City DPRD, must be able to provide as much assistance as possible to the leaders and members of the Cimahi City DPRD. in fulfilling its duties Providing Council services and synergizing working relations between the executive and the legislature to create an enabling environment. Planning, reviewing and coordinating formulating DPRD leadership guidelines, advancing the administration of all work units, organizing court cases and making minutes of meetings held by DPRD, maintaining and developing rules of conduct, and organizing administration and secretariat for DPRD regional representatives. the city council of the legislature is safe. The DPRD Secretariat in carrying out its main tasks and functions is always influenced by the strategic environment, conditions, situations, circumstances, events and influences that surround and influence the development of the achievement of organizational goals. The strategic environment is structured in the form of the organization's internal environment consisting of two strategic factors, namely strengths and weaknesses, and the organizational environment consisting of two strategic factors, namely opportunities and threats. Critical Success Factors Critical Success Factors are very important success factors in achieving organizational goals and objectives.